The Tongkungon: A Traditional KadazanDusun Plucked Musical Instrument from Sabah, Malaysia - Sinin Hamdan; Khairul Anwar Mohamad Said; Kuryati Kipli; Ezra A. M. Duin; Aaliyawani E. Sinin (BioResources, 2024)
This study highlights the sound analyses in a studio settings for a KadazanDusun bamboo musical instrument from Sabah Malaysia called the tongkungon. The tongkungon is a type of chordophone built from betung bamboo trees, which are found growing close to rivers and also known as ‘poring’ in Sabah, Malayisa. It is also a plucked idiochordal  bamboo tube zither. To adjust the pitches of the strings, the wedges can be shifted to shorten or lengthen them.The tongkungon sound radiator is made up of six strings with unique and innovative sound reproduction capabilities. Fast Fourier Transform (FFT) analysis was used to evaluate the frequency spectrum via a PicoScope oscilloscope. Adobe Audition was used to produce the time frequency analysis (TFA) spectrograms. The results showed the notes of the tongkungon strings 1, 2, 3 ,4, 5, and 6 to be C, E, B, A, F, and A, respectively. The tongkungon was tuned in the pentatonic scale F, A, B, C, and E. The 1st, 2nd, 3rd, 4th, 5th, and 6th strings were C4(261.63Hz), E4(329.63Hz), B3(246.94Hz), A3(220.00Hz), F3(174.61Hz), and A3(220.00Hz), respectively, i.e., with both 4th and 6th strings in A3. The frequency spectrum showed distinct fundamental and overtones frequencies. The first octave behaved as a multiple integer of the fundamental frequency for all strings. The number of partials in each string was inconsistent due to non-uniform thickness of the raised fibres from the bamboo tube.